Nilai-nilai Edukatif dalam Ungkapan Kepercayaan Rakyat di Nagari Luak Kapau Kecamatan Pauh Duo Kabupaten Solok Selatan - Putri, Hesti Fiska; Ermanto, Ermanto; Hamidin, Hamidin (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
This researcha ims to describe the educational values ​​embodied in the expression is purpose trust in Nagari Luak Kapau Pauh Duo Solok Selatan. The data of this research is the educational values ​​in the expression of people's trust. Data was collected through observation, interviews with community members and community leaders Nagari Luak Kapau Pauh Duo Solok Selatan. Data analysis was conducted descriptively. The results of research showed that 79 expression was found to contain educational value​​s. 79 of this expression, are found 17 phrases that contain the value of character education, 16 a phrase that contains the value of social education, 7 expression containing the value of beauty and aesthetic education, then 39 phrase that contains the value of family welf are education.